A Multilayered Mesoporous Gold Nanoarchitecture for Ultraeffective Near‐Infrared Light‐Controlled Chemo/Photothermal Therapy for Cancer Guided by SERS Imaging. Issue 6 (2nd January 2023) - Yin, Bohan; Ho, Willis Kwun Hei; Xia, Xinyue; Chan, Cecilia Ka Wing; Zhang, Qin; Ng, Yip Ming; Lam, Ching Ying Katherine; Cheung, James Chung Wai; Wang, Jianfang; Yang, Mo; Wong, Siu Hong Dexter
Abstract: Surface‐enhanced Raman scattering (SERS) imaging has emerged as a promising tool for guided cancer diagnosis and synergistic therapies, such as combined chemotherapy and photothermal therapy (chemo‐PTT). Yet, existing therapeutic agents often suffer from low SERS sensitivity, insufficient photothermal conversion, or/and limited drug loading capacity. Herein,  a multifunctional theragnostic nanoplatform consisting of mesoporous silica‐coated gold nanostar with a cyclic Arg‐Gly‐Asp (RGD)‐coated gold nanocluster shell (named RGD–pAS@AuNC) is reported that exhibits multiple "hot spots" for pronouncedly enhanced SERS signals and improved near‐infrared (NIR)‐induced photothermal conversion efficiency (85.5%), with a large capacity for high doxorubicin (DOX) loading efficiency (34.1%, named RGD/DOX–pAS@AuNC) and effective NIR‐triggered DOX release. This nanoplatform shows excellent performance in xenograft tumor model of HeLa cell targeting, negligible cytotoxicity, and good stability both in vitro and in vivo. By SERS imaging, the optimal temporal distribution of injected RGD/DOX–pAS@AuNCs at the tumor site is identified for NIR‐triggered local chemo‐PTT toward the tumor, achieving ultraeffective therapy in tumor cells and tumor‐bearing mouse model with 5 min of NIR irradiation (0.5 W cm −2 ). This work offers a promising approach to employing SERS imaging for effective noninvasive tumor treatment by on‐site triggered chemo‐PTT. Abstract : A multilayered mesoporous gold nanoarchitecture (RGD/DOX−pAS@AuNC) labeled with Raman reporters for surface‐enhanced Raman spectroscopy (SERS) imaging‐guided synergistic therapy toward cancer is reported. This nanoplatform enables efficient xenograft tumor of HeLa cell targeting with ultraeffective SERS imaging for tumor site and optimal therapeutic time point identification, as well as near‐infrared triggered photothermal therapy and hyperthermia enhanced chemotherapy.